2013
DOI: 10.1149/2.001403jss
|View full text |Cite
|
Sign up to set email alerts
|

Bionanoelectronics Platform with DNA Molecular Wires Attached to High Aspect-Ratio 3D Metal Microelectrodes

Abstract: In this study, the investigation of attachment of DNA molecular wires and ropes to high aspect-ratio three-dimensional (3D) metal microelectrodes and their subsequent electrical characterization as part of a bionanoelectronics platform is reported. The 3-D microelectrode architecture consists of mainly high aspect-ratio microelectrode structures (75 μm height and above) patterned from relatively thick layers of negative tone photoresist and covered by sputtered gold on their top surface. DNA attachments on 3-D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Glassy carbon (GC) is a very attractive material for use in neural interfaces as it has been demonstrated to have good electrical properties, to be chemically inert and electrochemically stable, and amenable to being fabricated into a variety of geometries25262728293031. However, only recently has GC been considered for such a use, mainly due to new enabling technologies that allow for pattern transfer and the integration of GC electrodes into thin-film polymeric substrates192021.…”
mentioning
confidence: 99%
“…Glassy carbon (GC) is a very attractive material for use in neural interfaces as it has been demonstrated to have good electrical properties, to be chemically inert and electrochemically stable, and amenable to being fabricated into a variety of geometries25262728293031. However, only recently has GC been considered for such a use, mainly due to new enabling technologies that allow for pattern transfer and the integration of GC electrodes into thin-film polymeric substrates192021.…”
mentioning
confidence: 99%
“…Lithography of microelectrodes, that form component of the bionanoelectronics chip shown in Fig. 2, consists of the traditional negative photolithography processes [21,[35][36][37].…”
Section: Microfabricationmentioning
confidence: 99%
“…Electrical resistance measurements were performed on the microelectrode structures where l-DNA was successfully attached. The AC electrical characterisations of the DNA molecular wire were carried out in a dry environment after washing the chip with DI water [21]. Typically, about 2-3 hours are needed before stable measurements can be recorded.…”
Section: Ac Electrical Characterisation Of Dna Molecular Wiresmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover the triangular shape of the electrode facilitated the chance of a single molecule being bridged between the electrodes. Recently, Vahidi 25 , et al confirmed that triangular metal electrodes were the most suitable form of electrode configuration which would result in attachment of DNA molecules at the electrodes with high aspect ratio. Figure 7 shows SEM images of λ-DNA being bridged between two metal electrodes.…”
mentioning
confidence: 99%